The Effectiveness of Emotional Release Technique (EFT) in Reducing Anxiety in Patients with Post-Traumatic Stress Disorder - Alamdar Baghini, Ayda; mohammadtehrani , hassan; Behboodi , Maasuomeh; Kiamanesh , Alireza (Journal of Assessment and Research in Applied Counseling (JARAC), 2021)
Background and Aim: Emotional release is a new technique based on acupuncture and cognitive therapy that plays an essential role in eliminating energy disorders in the body and helping individual recovery. The present study aimed to determine the effectiveness of the emotional release technique in reducing anxiety in patients with post-traumatic stress disorder. Methods: The present quasi-experimental study had experimental and control groups with a pretest-posttest and a two-month follow-up design. The statistical population consisted of 486 patients who visited Kerman Nourieh Psychiatric Hospital in 2018 and were hospitalized for post-traumatic stress disorder diagnosed by a psychiatrist. Among them, we selected 30 men with the inclusion criteria using the purposive sampling method and randomly assigned them to the experimental group (15 males) and the control group (15 males). The participants in the experimental group received six one-hour sessions as the Church emotional release technique (2014). All participants were assessed at the pre-test, post-test, and follow-up stages using the Spielberger anxiety inventory (1983). We analyzed data using the repeated-measures analysis of variance. Results: The results indicated that state anxiety (F=14.23, P= 0.008) and trait anxiety (F=3.07, P= 0.031) decreased in the experimental group and the effect remained stable in the follow-up phase. Conclusion: Since the intervention of the emotional release technique decreased anxiety in people with post-traumatic stress by targeting the release of emotions, we suggest clinicians use the emotional release technique to reduce anxiety in individuals.